Agronomic performance of ‘BRS’ Itaim cowpea beans at different planting densities under no-tillage and conventional systems - Cardoso, Milton (2017)
Cowpea beans play an important role in Brazilian farming, mainly in northern and northeastern regions, where it is widely grown among smallholder farmers. In recent years, commercial farmers have expanded its cultivation, mostly to the Midwest. This study aimed at evaluating the planting density of ‘BRS Itaim’ black-eyed cowpea beans under conventional (CT) and no-tillage (NT), with 75% mulch in the first year. Two experiments (CT and NT) were conducted at Embrapa Meio-Norte in Teresina - PI (Brazil), during the 2014/2015 harvest. Both experiments were carried out in a randomized block design with four replicates, considering the planting densities (PD) 12, 16, 20, 24, and 28 plants m-2. In both systems, grain yields (GY) and the number of pods per unit area (NPA) responded quadratically to an increase in PD, while a linear decreasing response was observed for the number of pods per unit area. The maximum grain yields (GY) were 1,492 kg ha-1 (23.8 plants m-2) and 1,136 kg ha-1 (23.2 plants m-2) under CT and NT, respectively. The NPA was most correlated with GY, presenting a value of 0.74 (P<0.01). The survival rate of cowpea seedlings was 94% under CT and 88% under NT. This larger reduction under NT might be attributed to a higher incidence of fungi in the soil under this system (e.g. Furasium solani, Fusarium oxysporum, Macrophomina phaseolina, Pythium spp, Sclerotium rolfsii and Rhizoctonia solani).